The use of TikTok as Japanese learning media - Fitrianingsih, Fitrianingsih; Nurjaleka, Lisda (Universitas Dian Nuswantoro, 2023)
In this technological era, social media has an important role in all fields. Various types of social media are used by the public, one of which is TikTok. TikTok's diverse video content provides benefits for its users. One type of video content that can be found on TikTok is learning video content that can be used as an alternative learning resource or learning media. One of the many learning video content found on TikTok is language learning video content. For example, Japanese language learning video content. The learning video content needs to be sorted first so that its use can be maximized. For this reason, this study aims to determine the type of learning and the level of Japanese language profiency contained in the Japanese language learning video content on TikTok. The method used in this study is a qualitative descriptive method which is providing detailed and factual data interpretation. Based on the research, there are 7 types of Japanese language learning (Aisatsu, Bunka, Bunpou, Goi, Kaiwa, Linguistics, and Moji) that can be found on TikTok video content. Meanwhile, the level of Japanese language proficiency that be found is level A1 to level B2 and level N5 to level N1.